2021
DOI: 10.1158/0008-5472.can-20-2121
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Cancer Progression by CDK4/6 Plays a Central Role in DNA Replication and Repair Pathways

Abstract: Although the cyclin-dependent kinases CDK4 and CDK6 play fundamental roles in cancer, the specific pathways and downstream targets by which they exert their tumorigenic effects remain elusive. In this study, we uncover distinct and novel functions for these kinases in regulating tumor formation and metastatic colonization in various solid tumors, including those of the breast, prostate, and pancreas. Combining in vivo CRISPR-based CDK4 and CDK6 gene editing with pharmacologic inhibition approaches in orthotopi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Our data indicated that ZC-22 notably induced formation of γH2A.X foci in breast and ovarian cancer cells ( Figure 3 D,E). Interestingly, ZC-22 induced stronger DNA damage responses (as indicated by the level of γH2A.X and percentage of cells positive for γH2A.X foci) than Olaparib ( Figure 3 C–E), which was consistent with the previous studies showing that CDK4/6 inhibition impaired HR pathway [ 30 , 31 , 32 ] and consequently aggravated PARPi-induced DNA damage.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our data indicated that ZC-22 notably induced formation of γH2A.X foci in breast and ovarian cancer cells ( Figure 3 D,E). Interestingly, ZC-22 induced stronger DNA damage responses (as indicated by the level of γH2A.X and percentage of cells positive for γH2A.X foci) than Olaparib ( Figure 3 C–E), which was consistent with the previous studies showing that CDK4/6 inhibition impaired HR pathway [ 30 , 31 , 32 ] and consequently aggravated PARPi-induced DNA damage.…”
Section: Resultssupporting
confidence: 91%
“…Recently, therapeutic synergy for combination of CDK4/6i and PARPi has been demonstrated in various solid tumors, including those of the breast, ovarian, and pancreas [ 22 , 23 , 48 ], which provides a promising approach for treatment of these cancers regardless HR status. In fact, current evidences indicate that inhibition of CDK6 but not CDK4 results in defective DNA repair and increased DNA damage, suggesting a role of CDK6 in controlling DNA replication and repair processes [ 30 ]. All together, these studies support our findings that combination of CDK4/6 and PARP inhibition by ZC-22 displays anti-tumor efficacy in breast and ovarian cancers beyond HR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…First, we find that CDK4/6 are overexpressed in a variety of tumor tissues, including OC, and that high expression of CDK4/ 6 is associated with a poor prognosis in OC patients. Dai et al propose that CDK4 regulates prometastatic inflammatory cytokine signaling, whereas CDK6 mainly controls DNA replication and repair processes, indicating that CDK4 and CDK6 facilitate tumor growth and progression in multiple cancers (18).…”
Section: Discussionmentioning
confidence: 99%
“…These targets are mainly regulatory factors related to inflammation, DNA replication and repair, cellular senescence, cell cycle, and so forth. [29][30][31][32] Myocardial fibrosis is one of the important mechanisms for the occurrence of AF, and these proteins may indirectly participate in the regulation of AF through myocardial fibrosis. The greatest number Overactivation of TP53 pathway in cardiomyocytes induces myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%